Budgeting for efficiency? A case study of the public K-12 education systems of Canada. Issue 34 (21st July 2019) - Mou, Haizhen; Atkinson, Michael M.; Marshall, Jim
ABSTRACT: In spite of the declining and uneven performance of Canadian students on the OECD's Programme for International Student Assessment (PISA) tests, little attention has been paid to whether provinces are allocating their education budgets to improve academic performance. This study uses a two-stage data envelope analysis (DEA) technique to estimate the degree to which education expenditures are efficiently allocated relative to achievement scores. We find that in these terms the overall cost-efficiency of the public K-12 education systems in the 10 provinces has deteriorated and that, in general, the provinces have become less able to allocate resources efficiently and use them in the most technically productive way. However, some provinces are more efficient than others. To gauge the extent to which performance measures, such as PISA scores, factor into budgeting decisions we interviewed 28 budget managers in 10 Canadian provinces and two territories, probing the criteria used to allocate education resources. The preponderant pattern of budgeting is described as an 'increments-based-on-formula' approach, one that is not particularly responsive to efficiency concerns but that often takes account of equity imperatives.